Middle Eocene to early Oligocene calcareous nannofossil biostratigraphy at IODP Site U1333 (equatorial Pacific) - TOFFANIN, FEDERICA; AGNINI, CLAUDIA; RIO, DOMENICO; Acton G.; Westerhold T. (2013)
We present a biostratigraphic and biochronologic study of calcareous nannofossils of middle Eocene - early Oligocene age recovered during IODP Expedition 320, at Hole U1333C in the equatorial Pacific Ocean. The study succession encompasses nannofossil Zones NP16–NP21 (equivalent to CP13–CP16) and Chrons C20r–C12r (middle Eocene-early Oligocene). The distribution patterns of calcareous nannofossil taxa are studied by means of relative abundance and semiquantitative counts with the final aim to test the reliability of biohorizons used in the Paleogene standard biozonations (Martini 1971; Okada and Bukry 1980) and check alternative bioevents included in a more recent mid-latitudes biostratigraphic scheme (Fornaciari et al. 2010). Calibration ages are estimated based on the ranges of the biozones relative to a detailed magnetostratigraphy constructed for the site. Of particular biostratigraphic significance, our study shows that the Top of Sphenolithus furcatolithoides, the Base of common and continuous occurrence (Bc) of Dictyococcites bisectus and the total range of Sphenolithus obtusus can be used to better constrain the middle Eocene interval. The studied sediments cover the crucial time period that followed maximum Cenozoic warmth and led up to the initial major glaciation on Antarctica, including two important climatic events, the Middle Eocene Climatic Optimum (MECO), a transient episode of global warming during a long-term cooling trend, and the Oi-1 event. The peculiar regime in sedimentation observed in the equatorial Pacific, which roughly consists of alternating phases of Carbonate Accumulation Events (CAE) and crashes in carbonate content, are correlated with increases and decreases in calcareous nannofossil abundances. A more detailed comparison indicates that the MECO corresponds to an interval with very low carbonate in between CAE3 and CAE4. This event is correlative with the Top of S. furcatolithoides, the Bc of D. bisectus and a prominent increase in the relative abundance of heavy calcified ...